Reversible morphology control of three-dimensional block copolymer nanostructures by the solvent-annealing-induced wetting in anodic aluminum oxide templates. Issue 13 (1st September 2016) - Chu, Chiang-Jui; Cheng, Ming-Hsiang; Chung, Pei-Yun; Chi, Mu-Huan; Jeng, Kai-Sheng; Chen, Jiun-Tai
ABSTRACT: In this work, the authors study the fabrication of three-dimensional block copolymer nanostructures in which the morphologies can be reversibly controlled. Polystyrene- block -polydimethylsiloxane (PS- b -PDMS), a promising candidate for nanolithography, is introduced into cylindrical nanopores of anodic aluminum oxide (AAO) templates using a solvent annealing–induced nanowetting in templates (SAINT) method. Not only the morphologies of the infiltrated PS- b -PDMS nanostructures can be tuned by the annealing solvents, but also the solvent-vapor-controlled morphologies can be altered reversibly by annealing the samples repeatedly between different solvent vapors. GRAPHICAL ABSTRACT: